Preparation, Characterization, and Antioxidant Activity of L-Ascorbic Acid/HP-β-Cyclodextrin Inclusion Complex-Incorporated Electrospun Nanofibers - Nabab Khan; Amit Kumar Singh; Ankit Saneja (Foods, 2023)
L-Ascorbic acid (LAA) is a key vitamin, implicated in a variety of physiological processes in humans. Due to its free radical scavenging activity, it is extensively employed as an excipient in pharmaceutical products and food supplements. However, its application is greatly impeded by poor thermal and aqueous stability. Herein, to improve the stability and inhibit oxidative degradation, we prepared LAA-cyclodextrin inclusion complex-incorporated nanofibers (NFs). The continuous variation method (Job plot) demonstrated that LAA forms inclusions with hydroxypropyl-β-cyclodextrin (HP-β-CD) at a 2:1 molar stoichiometric ratio. The NFs were prepared via the single step electrospinning technique, without using any polymer matrix. The solid-state characterizations of LAA/HP-β-CD-NF via powder x-ray diffractometry (PXRD), Fourier-transform infrared (FT-IR) analysis, differential scanning calorimetry (DSC), thermal gravimetric analysis (TGA), and nuclear magnetic resonance (1H NMR and 2D-NOESY) spectroscopy, reveal the effective encapsulation of the LAA (guest molecule) inside the HP-β-CD (host) cavity. The SEM micrograph reveals an average fiber diameter of ~339 nm. The outcomes of the thermal investigations demonstrated that encapsulation of LAA within HP-β-CD cavities provides improved thermal stability of LAA (by increasing the thermal degradation temperature). The radical scavenging assay demonstrated the enhanced antioxidant potential of LAA/HP-β-CD-NF, as compared to native LAA. Overall, the study shows that cyclodextrin inclusion complex-incorporated NFs, are an effective approach for improving the limitations associated with LAA, and provide promising avenues in its therapeutic and food applications.